Chondroblastic osteosarcoma mimicking periapical abscess - Fernanda Paula YAMAMOTO-SILVA; Brunno Santos de Freitas SILVA; Aline Carvalho BATISTA; Elismauro Francisco de MENDONÇA; Décio dos Santos PINTO-JÚNIOR; Carlos ESTRELA
Abstract Lesions of non-endodontic origin may mimic periapical abscess. Osteosarcoma is a rare malignant lesion. Case report The present report describes a case of chondroblastic osteosarcoma in the periapical region of teeth #29, #30, and #31 of an 18-year-old male. Clinical history showed self-reported discomfort in the right posterior gingiva for over a month. Physical examination showed a small expansion and redness of the right mandibular buccal and lingual cortical plates, but no signs of pain or inflammation were observed. All the teeth responded positively to pulp sensibility. Periapical and panoramic radiographs showed slight periapical radiolucency in the roots of teeth #29 and #30, clear periodontal ligament space widening, and evident loss of lamina dura. Incisional biopsy was performed, and based on microscopic findings the diagnosis of chondroblastic osteosarcoma was confirmed. Conclusions Non-endodontic diseases associated with tooth root apex, such as chondroblastic osteosarcoma, should be included in differential diagnosis of jaw lesions that resemble periapical abscess.